Model Pemberdayaan Anggota Koperasi Sebagai Upaya Pencegahan Kredit Bermasalah Pada Koperasi Simpan Pinjam Credit Union Bahtera Sejahtera Tempat Pelayanan Kewapante - Dalo Soba, Alfredo Marsis; Mitan, Wihelmina; Kolit, Yuliana Anggreani Dua Delang (Universitas Nusa Nipa Maumere, 2026)
This study aims to analyze the model of cooperative member empowerment at the Credit Union Savings and Loan Cooperative Bahtera Sejahtera, Kewapante Service Unit, with a focus on two main indicators: cooperative member empowerment and efforts to prevent non-performing loans. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results of the study indicate that the management of the Credit Union Savings and Loan Cooperative Bahtera Sejahtera, Kewapante Service Unit, has implemented an empowerment model based on enhancing members’ capacities through various programs, including basic education, financial literacy training, specialized education, entrepreneurship education, refresher training, the formation of territorial groups and assisted member groups, as well as mentoring for business groups. Although there is not yet a formal theoretical framework or binding regulation governing the empowerment model implemented, the empowerment practices carried out by the cooperative have contributed to improving members’ capacities in managing their finances and businesses, particularly for members experiencing non-performing loans. This finding demonstrates that the cooperative member empowerment model implemented at the Credit Union Savings and Loan Cooperative Bahtera Sejahtera, Kewapante Service Unit, serves as a strategic instrument in preventing the occurrence of non-performing loans.